The Effect of Compensation and Organizational Culture on the Performance of Employees in the Culture of Medan City - Dinaria br Sembiring; Bena br Ginting (Jurnal Mantik, 2021)
The research was conducted to find out how the influence of compensation and organizational culture on the performance of employees of the Medan City Culture Service. This study uses three variables consisting of the dependent variable, namely Employee Performance (Y), while the independent variables are compensation (X1) and organizational culture (X2). This study uses explanatory research methods through associative research, namely research that aims to explain the influence between two or more variables. The population in this study were all 38 employees of the Medan City Culture Service with the status of civil servants. Methods of data collection is done by literature study questionnaire, and observation. Data analysis carried out in this study was hypothesis testing with t test (partial test) and F test (simultaneous test). The results of this study showed that: (1) based on the partial test, compensation has an effect on the performance of Medan City Culture Service employees with a t-test of 3,724. (2) Based on the partial test, organizational culture affects the performance of Medan City Culture Service employees with a t-test of 4,065. (3) Based on the Simultaneous Test of the Effect of Compensation and Organizational Culture on the Performance of Medan City Culture Service Employees with an F test of 61,318